Desempenho de sementes recobertas com fósforo - Peske, Fabrício Becker (2008)
The seed is the starting point to obtain a uniform plant population, a good field, and thus, a remarkable productivity. From this concept, new technologies and advances appear more an more each day, capable of changing the way of looking at the global agriculture. The seed coating has a great potential to become a strong factor on the seed sector. It allows the seed producers to add a vast variety of materials on the seed. Having all this in mind, this project had the objective of studying the effects of phosphorous sources added to the soybean seeds trough coating. It involved 4 doses of Phytic Acid and 4 doses of Bicalcic phosphate, which were: 0g, 0,7g, 1,4 e 2,1g / 100g of seeds and two types of soil. The experiment was developed by a randomized complete block design with three replications. It was used vases with 12 kg of capacity with three plants per experimental units. The evaluations were number of seed per plants, weight of seeds per plants and weight of 1000 seeds. Based on the results the following conclusions were taken 1- The Seed Coating of soybeans along with phosphorous and depending on doses and phosphorous sources, increases yield; 2 The dosage of 21 grams of Phytic Acid per 1 kilo of seeds increases yield in about 14% on total grains weight.